CFD Application To Eliminate Delamination Defects In Flange Products - Aep Supriatna (Jurnal Indonesia Sosial Teknologi, 2024)
Delamination defects in breather pipe of flange products produced through the injection molding process are a critical issue that affects product performance. The objective of this study is to reduce the detected delamination rate by 3.77% from a total of 2173 production units, with a maximum allowable limit of 0.5%. The method applied includes identifying the cause of delamination through analysis by collecting defect data, analyzing through CFD (Computation fluid dynamic) method, and observing mold conditions. The proposed solution focuses on improving the slider motion mechanism of the mold and adding a gas vent with a vacuum system. Test results showed that these improvements succeeded in reducing the delamination rate to 0%. Further evaluation through X-ray analysis and microscopic checking confirmed no significant voids in the breather pipe and the integrity between material layers. The conclusion of this study confirms that foreign material, in the form of plastic debris and gas burn deposit injected due to slider mechanism failure and lack of gas vent, is the main factor causing delamination. This study is expected to provide comprehensive guidance for the industry in addressing similar issues in the future.